National Health Service Bury and Rochdale Doctors on Call (NHS BARDOC): Medical Students Working on the Frontline at the Greater Manchester COVID-19 Death Service - Yaqub, Imania; Ghafoor, Bilaal (International Journal of Medical Students, 2020)
We were third year medical students preparing for our clinical examinations to take place. What felt like a few moments later, on the 23rd of March 2020 Greater Manchester went into lockdown and we were told to stay home to protect the NHS and prevent the spread of the COVID-19 virus. Like many students across the UK, we seeked a job within the NHS to decrease the demand for staff during the pandemic. We worked on the frontline for an Emergency Community Death Service set up in response to the rapid increase in deaths occurring in the community due to the pandemic. Here we arranged for timely and efficient verification of the deaths alongside handling the legalities of the Medical Certificate of Cause of Death and cremation papers. It was a psychologically challenging, but massively rewarding journey.